Long-Term Consequences of Extended Endocrine Strategies for Premenopausal Breast Cancer [11OP]. Issue 1 (May 2017) - Kwon, Janice S.; Pansegrau, Gary; Nourmoussavi, Melica; Hammond, Geoffrey; Carey, Mark
Abstract : INTRODUCTION: Breast cancer is the most common cancer among women in America, and gynecologists often encounter these women in their practice. After 5 years of adjuvant tamoxifen, women with ER+ breast cancer benefit from extended endocrine therapy, either with tamoxifen or an aromatase inhibitor (AI). For premenopausal women, ovarian ablation (OA) is required before starting an AI, but there is concern about the long-term outcomes (osteoporosis, heart disease) and costs of OA. METHODS: A Markov Monte Carlo simulation model estimated the costs and benefits of extended endocrine strategies in a hypothetical cohort of premenopausal women with ER+ cancer: (1) no further treatment; (2) tamoxifen for 5 years; (3) OA followed by AI for 5 years (OA/AI). Effectiveness was measured in years of life expectancy gain. Monte Carlo simulation estimated the number of adverse events and deaths from each strategy in the American population over a 40-year horizon. RESULTS: Tamoxifen for 5 more years yielded a higher average discounted life expectancy gain than OA/AI (16.57 vs. 16.34 years) at lower average cost ($2, 976 vs. $10, 150). For 18, 000 ER+ premenopausal women diagnosed annually, the simulation estimated 12, 526, 11, 508, and 10, 289 deaths after no further treatment, tamoxifen and OA/AI respectively, but another 2, 139 deaths from long-term consequences of OA. According to sensitivity analyses, women had to be over 50.8 years of age before OA/AI became cost-effective. CONCLUSION: As extended endocrine therapy for premenopausal ER+ breast cancer, another 5 years of tamoxifen is more effective and less costly than ovarian ablation followed by 5 years of aromatase inhibitor.